Muddying the waters coauthoring feminisms across scholarship and activism - Nagar, Richa (Dissident feminisms, 2014)
"In Muddying the Waters, Richa Nagar uses stories, encounters, and anecdotes as well as methodological reflections, to grapple with the complexity of working through solidarities, responsibility, and ethics while involved in politically engaged scholarship. Experiences that range from the streets of Dar es Salaaam to farms and development offices in North India inform discussion of the labor and politics of co-authorship, translation and genre blending in research and writing that cross multiple...and often difficult...borders, Nagar links the implicit assumptions, issues, and questions involved with scholarship and political action, and explores the epistemological risks and possibilities of creative research that brings these into intimate dialogue. Daringly self-conscious, Muddying the Waters reveals a politically engaged research and writer working to become "radically vulnerable," and on the ways a focus on such radical vulnerability could allow a re-imagining of collaboration that opens new avenues to collective dreaming and laboring across sociopolitical, geographical, linguistic, and institutional borders"..